Dampak Pembiayaan BUS dan UUS Terhadap Produk Domestik Bruto Indonesia Berdasarkan Lapangan Usaha - Aida Azmi Nabila; Endang Hatma Juniwati; Fifi Afiyanti Tripuspitorini (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Islamic banking has a role to encourage economic development and enhance economic growth. One way to do this is by allocating Islamic banking financing funds to all economic sectors or industrials in Indonesia. There is a mismatch between the growth statistics of financing distribution to Gross Domestic Product based on industrials consisting of seven industrial. This istudy iaims ito idetermine iwhether ior inot ithere iis ia relationship, iconstribution, and the effect iof ifinancing ichanneled on Indonesia's Gross Domestic Product. The isample iin ithis istudy was determined using ipurposive isampling. iThis iresearch imethod iis ia idescriptive imethod iwith ia iquantitative iapproach. iThe iresults iof the model test of the effect of BUS and UUS financing on Indonesia’s Gross Dometic Product based on the industrial in 2012-2019 show that not all financing has a relationship, constribution, and the effect to Indonesia’s Gross Domestic Product based on the industrial.